2003
DOI: 10.1051/0004-6361:20030978
|View full text |Cite
|
Sign up to set email alerts
|

The corona of HD 223460 (HR 9024)

Abstract: Abstract. HD 223460 (HR 9024), a chromospherically active late−type giant with a high X-ray luminosity, was observed by the XMM-Newton space observatory. Series of lines of highly ionized Fe and several Lyman lines of hydrogen-like ions and triplet lines of helium-like ions are visible in the reflection grating spectra, most notably from O and Ne. Analysis results suggest a scenario where the corona of HD 223460 is dominated by large magnetic structures similar in size to interconnecting loops between solar ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 68 publications
2
12
0
Order By: Relevance
“…OU And is a well known active red giant, with small rotation period for a giant (24.2 d, Strassmeier et al 1999) and very active in X-rays (Gondoin et al 2003, Ayres et al 2007). In the literature is given a T eff value inferred for OU And by Wright et al (2003) from its spectral type.…”
Section: B123 Ou and Hd 223460mentioning
confidence: 99%
“…OU And is a well known active red giant, with small rotation period for a giant (24.2 d, Strassmeier et al 1999) and very active in X-rays (Gondoin et al 2003, Ayres et al 2007). In the literature is given a T eff value inferred for OU And by Wright et al (2003) from its spectral type.…”
Section: B123 Ou and Hd 223460mentioning
confidence: 99%
“…Spectral type, bolometric luminosity, effective temperature, radius, mass and X-ray luminosity in the 0.3-10 keV band of the sample stars. References to X-ray data (last column) are as follows: (1) Maggio et al (1990); (2) Hünsch et al (1998); (3) Gondoin (2003a); (4) Gondoin (2002); (5) Gondoin (2005); (6) Gondoin (2004); (7) Gondoin (2003b). substantially.…”
Section: Sample Selectionmentioning
confidence: 99%
“…OU And is chromospherically active with X-ray luminosity variations. Series of highly ionised iron lines, several Lyman lines of hydrogenlike ions and triplet lines of Helium-like ions in the X-ray region (Gondoin 2003;Ayres et al 2007) are observed in its spectra.…”
Section: Introductionmentioning
confidence: 99%